Effect of Pelvic Rocking Technique on the Relief of Low Back Pain among Multigravida Pregnant Women - Suwanti Suwanti; Yunita Marliana; Irni Setyawati (EMBRIO: Jurnal Kebidanan, 2023)
In third trimester of pregnancy, one of the problems that often arise is back pain. Back pain in pregnant women can be relieved by pelvic rocking exercise performed in a standing, sitting and lying position, both in pairs with the husband or one of the other family members. This study aims to determine the effect of pelvic rocking technique on the relief of low back pain among multigravida pregnant women. This was a pre-experimental study with pre-test and post-test non-equivalent control group design. The study was conducted at Cakranegara Community Health Center. The study samples involved 30 multigravida pregnant women. The statistical test applied here was Wilcoxon test. The results showed that regarding characteristics of respondents, most of them were in the non-risky age group by 23 respondents (76.7percent), had low education by 29 respondents (96.7percent), were unemployed (Housewives) by 25 respondents (83.3percent), had normal BMI by 18 respondents (60.0percent), had normal weight by 18 respondents (60,0percent), had a parity of more than 2 by 18 respondents (66.7percent) and were in the 25-38 weeks of gestation by 28 respondents (93.3percent). After the implementation of pelvic rocking technique, there was a decrease in mean low back pain score by 1.47. Wilcoxon test result obtained a P value of 0.00001. Pelvic rocking technique could relieving low back pain among multigravida pregnant women.